Migration, multilingualism and education Critical perspectives on inclusion - Mary, Latisha; Krüger, Ann-Birte 1974-; Young, Andrea S. (New perspectives on language and education, 2021)
This book addresses the question of how equitable and inclusive education can be implemented in heterogeneous classes where learners' languages and cultures reflect the social reality of mass migration and everyday plurilingualism. The book brings together researchers and practitioners to address language policy and pedagogy